Tablets of “Hydrochlorothiazide in Cyclodextrin in Nanoclay”: A New Nanohybrid System with Enhanced Dissolution Properties - Maestrelli, Francesca (Pharmaceutics, 2020)
Hydrochlorothiazide (HCT), a Biopharmaceutical Classification System (BCS) class IV drug, is characterized by low solubility and permeability, that negatively affect its oral bioavailability, reducing its therapeutic efficacy. The combined use of cyclodextrins (CDs) and nanoclays (NCs) recently proved to be a successful strategy in developing delivery systems able to merge the potential benefits of both carriers. In this work, several binary systems of CDs or NCs with the drug were obtained, using different drug:carrier ratios and preparation techniques, and characterized in solution and in solid state, to properly select the most effective system and preparation method. Then, the best CD (RAMEB) and NC (sepiolite), at the best drug:carrier ratio, was selected for preparation of the ternary system by co-evaporation and emerged as the most effective preparation method. The combined presence of RAMEB and sepiolite gave rise to a synergistic improvement of drug dissolution properties, with a two-fold increase in the amount of drug dissolved as compared with the corresponding HCT-RAMEB system, resulting in an approximately 12-fold increase in drug solubility as compared with the drug alone. The ternary system that was co-evaporated was then selected for a tablet formulation. The obtained tablets were fully characterized for technological properties and clearly revealed a better drug dissolution performance than the commercial reference tablet (Esidrex(®)).